Blockchain technology adoption strategies for the shipping costs bearer in the fresh product supply chain - Weisi Zhang; Lin Wu; Lulu Ji (Frontiers in Sustainable Food Systems)
Fresh products are characterized by a certain deterioration rate, and the fresh supply chain typically relies on third-party cold chain logistics companies (3PLs) for transportation. This study constructs a fresh supply chain composed of supplier, retailer, and third-party cold chain logistics company, where shipping costs are borne by either the supplier or the retailer. The shipping costs bearer considers whether to adopt blockchain technology to enhance the transparency of fresh logistics and improve consumers’ perceived value. Using game theory, the paper attempts to explore who should bear the shipping costs (supplier or retailer), clarifying the shipping costs bear’s blockchain adoption strategy. The results indicate that: First, the 3PL’s profit is negatively correlated with the research and development (R&D) cost coefficient of carbon emission reduction (CER) and the deterioration rate of fresh products, while it is positively correlated with consumer low-carbon preferences. When the R&D cost coefficient of CER is high, or the deterioration rate of fresh products is low, or consumer low-carbon preferences are low, the 3PL prefers RCB model, otherwise SNB model. Additionally, the 3PL’s carbon reduction level is higher when blockchain technology is adopted, especially with low R&D cost coefficient of CER and high consumer low-carbon preferences. Second, regarding who should bear the shipping costs, when blockchain technology is not adopted, it is optimal for the supplier to bear the shipping costs, maximizing the overall profit of the supply chain. In contrast, when blockchain technology is adopted, having the retailer bear the shipping costs maximizes the overall profit of the supply chain. Specifically, when the R&D cost coefficient of CER is high, regardless of blockchain adoption, the supplier bearing the shipping costs maximizes the overall profit of the supply chain. Finally, concerning whether the bearer should invest in blockchain technology, when the R&D cost coefficient of CER is low and consumer low-carbon preferences are high, adopting blockchain technology leads to Pareto optimal profits for both the supplier and the retailer, regardless of who bears the shipping costs. This study provides a decision framework for optimizing cost allocation and technology adoption in sustainable cold chain management, particularly relevant for perishable goods with short shelf lives.